Molecular Docking Studies of Marine Sulfated Polysaccharides: Exploring Green Seaweed’s Role Against SARS-CoV-2 Spike Glycoprotein - Herida, Azalia Puspa; Kusumaningrum, Hermin Pancasakti; Zainuri, Muhammad; Sabdono, Agus; Subagiyo, Subagiyo; Wahyuningsih, Candra (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) is a virus responsible for the infectious disease of COVID-19 (Coronavirus Disease 2019), whose development is still being monitored. One way to deal with the virus’s development is by searching for natural-based medicines that prevent and treat SARS-CoV-2 infection. The abundant biodiversity can be used as a source of treatment. Among many natural resources, seaweed is one of the natural resources rich in bioactive components. Sulfated polysaccharide is one of the potential bioactive compounds in seaweed because it has antiviral effects and the potential to treat SARS-CoV-2. This research aims at increasing the potential of Karimunjawa green seaweed sulfate polysaccharides for antiviral capabilities in SARS-CoV-2 through molecular docking. This research began with identifying the morphology of Karimunjawa seaweed. Identify the components of sulfated polysaccharide compounds based on literature studies according to the species that have been identified. Analysis of the antiviral ability of SARS-CoV-2 based on its binding ability to the SARS-CoV-2 target protein through a molecular docking computational program and testing drug compounds using the Lipinski rule. Based on the research results, it is known that the seaweed obtained from Karimunjawa based on morphology, belongs to the genus Kappaphycus. Molecular docking with a ligand and spike glycoprotein (6LZG) resulted in the hexadecanoic acid compound having a binding free energy of -5.3 kcal.mol-1, which was the compound with the lowest yield compared to other test compounds. The prediction of the physicochemical properties of all test compounds fulfills Lipinski's five rules and has the potential to be used as medicinal compounds.